Rousseau's reader strategies of persuasion and education - Scott, John T., 1963- (The University of Chicago Press, 2020)
On his famous walk to Vincennes to visit the imprisoned Diderot, Rousseau had what he called an "illumination"--the realization that man was naturally good but becomes corrupted by the influence of society--a fundamental change in Rousseau's perspective that would animate all of his subsequent works. At that moment, Rousseau "saw" something he had hitherto not seen, and he made it his mission to help his readers share that vision through an array of rhetorical and literary techniques. In Rousseau's Reader, John T. Scott looks at the different strategies Rousseau used to engage and persuade the readers of his major philosophical works, including the Social Contract, Discourse on Inequality, and Emile. Considering choice of genre; textual structure; frontispieces and illustrations; shifting authorial and narrative voice; addresses to readers that alternately invite and challenge; apostrophe, metaphor, and other literary devices; and, of course, paradox, Scott explores how the form of Rousseau's writing relates to the content of his thought and vice versa. Through this skillful interplay of form and content, Rousseau engages in a profoundly transformative dialogue with his readers. While most political philosophers have focused, understandably, on Rousseau's ideas, Scott shows convincingly that the way he conveyed them is also of vital importance, especially given Rousseau's enduring interest in education. Giving readers the key to Rousseau's style, Scott offers fresh and original insights into the relationship between the substance of his thought and his literary and rhetorical techniques, which enhance our understanding of Rousseau's project and the audiences he intended to reach